Relationship Between Personal Hygiene and The Incidence of Vaginal Discharge (Fluor Albus) in Adolescent Girls in The DIII Nursing Study Program, Sidoarjo - Amelia, Erlin; Rahariyani, Loetfia Dwi; Utomo, Agus setyo (Global Ten Public Health and Nursing Journal, 2025)
Vaginal discharge is a discharge or fluid that comes out of the vaginal opening, excluding excess blood. Vaginal discharge can be normal (physiological) or abnormal (pathological) caused by an imbalance in the pH or acidity of the vagina. Cases of vaginal discharge are common among adolescent girls due to lack of knowledge, which has an impact on the attitude of not keeping the genital area clean properly and correctly. This study used a quantitative analytic type of research using a Cross Sectional approach. This study uses correlation research methods. The population in this study were young women in the Sidoarjo D3 Nursing Study Program. The results showed that the characteristics of respondents totaling 64 people obtained from the results of the study the majority of respondents aged 19-20 years and the majority of respondents' education level was level 3. Most of the young women in Prodi D3 Nursing Sidoarjo experience physiological vaginal discharge. Most of the young women in Prodi D3 Nursing Sidoarjo have poor personal hygiene. There is a relationship between personal hygiene and the incidence of vaginal discharge or fluor albus in adolescent girls in Prodi D3 Nursing Sidoarjo in 2023 with a p-value of 0.051 <0.10. Based on the researcher's analysis, there is a relationship between personal hygiene and the incidence of vaginal discharge in adolescent girls due to poor personal hygiene due to lack of knowledge and attention to personal hygiene in the genitalia area. Therefore, personal hygiene must be considered in order to prevent the occurrence of diseases, one of which is vaginal discharge.